The Effect of Financial Literacy, Self-Control, and Buy Now Pay Later (BNPL) Usage on Financial Decision-Making Among Generation Z: The Mediating Role of Financial Behavior - Vania Utami; Osly Usman (Journal of Digital Business and Global Economy, 2026)
By evaluating the mediating variable of financial behavior, this research investigates how financial literacy, self-control, and the usage of "Buy Now Pay Later" (BNPL) services affect financial decision-making among Generation Z. In this quantitative study, 163 members of Generation Z from the Jabodetabek region were surveyed to gauge their level of familiarity with or usage of BNPL services. An online questionnaire was used to gather data, which was then analyzed using PLS-SEM using SmartPLS 4. According to the study's findings, BNPL and financial literacy significantly impact people's ability to make sound financial decisions. Contrarily, there is little direct correlation between self-control and financial behavior and financial decision-making. In contrast to BNPL, the results show that financial knowledge and self-control considerably promote good financial conduct. Importantly, the study shows that financial behavior is not a moderating variable between financial decision-making and financial literacy, self-control, or BNPL use. Rather than being influenced by their everyday financial behavior routines, this study emphasizes that in the digital age, Generation Z's financial literacy and the use of digital credit facilities like BNPL are the primary drivers of their ultimate financial choices.